Impact of the COVID-19 Pandemic on the General Mental Health in Sweden: No Observed Changes in the Dispensed Amount of Common Psychotropic Medications in the Region of Scania - Wolfschlag, Mirjam; Grudet, Cécile; Håkansson, Anders (Frontiers in Psychiatry, 2021)
Some first investigations have focused on the consequences of the COVID-19 pandemic for the general mental health after its outbreak in 2020. According to multiple self-reporting surveys, symptoms of stress, anxiety, and depression have risen worldwide. Even some studies based on health care records start to be published, providing more objective and statistically reliable results. Additionally, concerns have been raised, to what extend the access to mental health care has been compromised by the COVID-19 outbreak. The aim of this study was to detect changes in prescription trends of common psychotropic medications in the Swedish region of Scania. The monthly dispensed amounts of selected pharmaceuticals were compared from January 2018 until January 2021, regarding the prescription trends before and after the outbreak of COVID-19. Using an interrupted time series analysis for each medication, no general trend changes were observed. On the one hand, a possible deterioration of the general mental health could not be confirmed by these results. On the other hand, the access to mental health care did not seem to be impaired by the pandemic. When interpreting findings related to the COVID-19 pandemic, regional differences and country-specific approaches for coping with the pandemic should be considered. The Swedish population, for instance, never experienced a full “lock-down” and within Sweden the time point of the outbreak waves differed regionally. In general, the effects of the COVID-19 outbreak on mental health are still unclear and need to be investigated further in an international comparison.